PKA Activates AMPK Through LKB1 Signaling in Follicular Thyroid Cancer - Kari, Suresh; Vasko, Vasyl V.; Priya, Shivam; Kirschner, Lawrence S. (Frontiers in Endocrinology, 2019)
Thyroid cancer affects about one percent of the population, and has seen rising incidence in recent years. Follicular thyroid cancer (FTC) comprises 10–15% of all thyroid cancers. Although FTC is often localized, it can behave aggressively with hematogenous metastasis, leading to an increased risk of cancer death. We previously described a mouse model for FTC caused by tissue-specific ablation of the Protein Kinase A (PKA) regulatory subunit Prkar1a, either by itself or in combination with knockout of Pten. Loss of Prkar1a causes enhanced activity of PKA, whereas ablation of Pten causes activation of Akt signaling. At the molecular level, these genetic manipulations caused activation of mTOR signaling, which was also observed in human FTC cases. To understand the mechanism by which PKA activates mTOR, we began by studying intracellular kinases known to modulate mTOR function. Although AMP-activated kinase (AMPK) has been characterized as a negative regulator of mTOR activity, our tumor model exhibited activation of both AMPK and mTOR. To understand the mechanism by which AMPK was turned on, we next studied kinases known to cause its phosphorylation. In this paper, we report that PKA leads to AMPK activation through the LKB1 kinase. Although LKB1 has traditionally been considered a tumor suppressor, our data indicates that it may have a complex role in the thyroid gland, where its activation appears to be frequently associated with follicular thyroid carcinoma in both mice and humans.